Analisis Pengaruh Faktor-Faktor Agency Cost Terhadap Kecenderungan Income Smoothing Pada Perusahaan Manufaktur Di Indonesia - Elan Kurniawan; Indah Ayu Tri Subekti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Income smoothing is a management effort to reduce the variation in the number of reported earnings to match the desired target by manipulating earnings through accounting methods or through transactions. Through multiple linear regression analysis is known that the variable company size, Debt To Equity Ratio (DER), Operating general administration (OGA)and Asset Turnover (ATO) has a significant influence on the practice of income smoothing. Adjusted R Square that shows value 0.112 indicates that 11.2% turning in income smoothing can be determined by the independent variables in this research, meanwhile the reminder 88.8% determined by other factors which not include this research. Parcial test showed that variable Net Debt o Equity ratio (DER) and Operating General Administration (OGA) has a significant influence on the practice of income smoothing. While the company size variable and Asset Turnover (ATO) has no effect on the practice of income smoothing